Competencies and scope of practice of nurse practitioners in primary health care: a scoping review protocol. Issue 4 (11th April 2021) - Schlunegger, Margarithe Charlotte; Aeschlimann, Simona; Palm, Rebecca; Zumstein-Shaha, Maya
ABSTRACT: Objective: The objective of this scoping review is to explore existing literature about nurse practitioners' competencies and scope of practice in primary health care in order to examine and conceptually map the evidence and identify gaps in the literature. Introduction: To meet growing health care needs, current primary health care models have expanded to include nurse practitioners. The integration of nurse practitioners in primary health care is challenging. This is mainly due to the lack of a unified definition of the role, competencies, or clear criteria to determine scope of practice. Inclusion criteria: This scoping review will consider studies addressing nurse practitioner practice in primary health care. The focus lies on nurse practitioner competencies (eg, core competencies or practice activities) and scope of practice (eg, areas of responsibility or legally defined professional boundaries). Studies that were conducted in primary health care settings in rural, urban, and suburban regions where nurse practitioners are employed will be included. Methods: Studies published in English, German, or French from 1965 to present will be considered. The databases to be searched include PubMed, CINAHL, Web of Science, and PsycINFO. Sources of unpublished studies and gray literature to be searched will include ProQuest Dissertations and Theses, OpenGrey, and websites of national nurse practitioner organizations. Retrieval of full-text studies and data extraction will be performed independently by two reviewers. The extracted data will be presented in tables or graphs, with an accompanying narrative summary.